Cohort Profile: The Zurich Project on the Social Development from Childhood to Adulthood (z-proso) - Ribeaud, Denis (Journal of developmental and life-course criminology, 2022)
The Zurich Project on the Social Development from Childhood to Adulthood (z-proso) began in 2004 in response to the need for a better evidence base to support optimal child social development and prevent crime and violence. Since then, the study has tracked the development of a diverse sample of youths (N = 1,675 in the target sample; ~50% female) from age 7 (n = 1,360) to age 20 (n = 1,180), with primary data collection waves at ages 7, 8, 9, 10, 11, 12, 13, 15, 17, and 20. The study uses a multi-method, multi-informant design that combines teacher, youth, and parent reports with observational and behavioural measures, biosampling, functional imaging, and ecological momentary assessment. Analyses of the data have contributed important evidence to a diversity of topics in child and adolescent development, illuminating the developmental roots of crime and aggression, the impacts of exposure to different forms and combinations of victimisation, and trajectories of mental health and neurodevelopmental symptoms.